The influence of social media marketing and reviews on purchase decisions for brand erigo - Keni Kaniawati; Bulan Maharani Sudrajat (Enrichment : Journal of Management, 2023)
Competition, more advanced technology, and shifting customer preferences. These entrepreneurs use a variety of sales strategies to advertise their goods, including social media marketing, among other promotional techniques. The purpose of this study is to determine how social media marketing for the Erigo brand affects consumers' decisions to buy, how reviews affect those decisions, and how social media marketing and reviews together affect those decisions. This research approach is quantitative. The results of the study showed that social media marketing and reviews jointly had a big impact on sales, with social media marketing having a strong impact on reviews and reviews having a considerable impact on purchases in part. The urgency of this research stems from its potential to offer actionable insights for businesses to capitalize on social media marketing and reviews in influencing consumers' purchasing decisions. By understanding the impact of these factors, businesses can develop more targeted and effective marketing strategies, enhance their brand reputation, and stay competitive in the digital marketplace.